The Analysis of Learning English by Using You Tube in Improving The LP3M Students Interest (AK-APIIC/ 2022) - Handayani, Cici (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Mastery of English is increasingly required for college graduates because they will face the real world of work which requires them to have various kinds of skills including expertise in English. As education practitioner, lecturer in private tertiary institutions must do some efforts to increase the interest of students in English so that learning English is easier to understand and the knowledge conveyed can be well mastered. One of the efforts is to use the You Tube media, which is capable of displaying interesting and creative English learning materials, which can be learned at any time to improve their ability both in listening, speaking, reading and writing. The role of lecturers with high creativity, and by delivery the materials that easy to understand and fun will certainly improve the results of learning English later. From the results of research on Learning English by Using You Tube in Improving The LP3M Students' Interest, it was found that You Tube was able to make students interested in learning English by 90% while teaching methods from lecturers was able to make students interested in learning English by 80%. The use of You Tube and good teaching methods by lecturers will certainly greatly increase students' interest in learning English and this will have a positive impact on the maximum knowledge that will be acquired by students later.